(untitled) (Analysis in Theory and Applications, 2017)
The aim of this paper is to give a simple proof of the restriction theorem for the maximal operators on the d-dimensional Euclidean space R^d, whose theorem was proved by Carro-Rodriguez in 2012. Moreover, we shall give some remarks of the restriction theorem for the linear and the multilinear operators by Carro-Rodriguez and Rodriguez, too.